The unintended benefit of the risk factor mandate of 2005 - Huang, Allen H.; Shen, Jianghua; Zang, Amy Y. (Review of Accounting Studies, 2022)
Abstract In 2005, the SEC mandated that firms disclose risk factors to provide useful information about firm risk. An unintended effect of the mandate is that mandatory risk factor (RF) disclosure may constitute “meaningful cautionary language” as defined in the Private Securities Litigation Reform Act, and may therefore provide legal protection for forward-looking statements (FLSs). Using both a difference-in-differences design and a two-stage least squares approach, we find that, following the mandate, firms that had not previously disclosed risk factors (late RF disclosers) became more willing to provide qualitative FLSs, particularly positive ones, than other firms. This finding is consistent with our prediction that, for late RF disclosers, the mandate reduces managers’ perceived litigation risk. We also find that these firms experience improvement in their information environment. A path analysis reveals that the mandate improves firms’ information environment not only directly but also indirectly by prompting more disclosure of positive FLSs, illustrating an unintended benefit of the 2005 RF mandate. Cross-sectional tests show that the RF mandate induces a larger increase in positive FLSs for firms whose managers perceive a higher level of benefit from safe harbor protection arising from meaningful cautionary statements.